Moringa oleifera leaf ethanolic extract benefits cashmere goat semen quality via improving rumen microbiota and metabolome - Liang, Jianyong; Wu, Tiecheng; Wang, Tao; Ma, Yuejun; Li, Yurong; Zhao, Shengguo; Guo, Yanli; Liu, Bin (Frontiers in Veterinary Science, 2023)
Background: Artificial insemination (AI) is an effective reproductive technique to improve the performance of cashmere goats and prevent the spread of diseases, and the quality of the semen determines the success of AI. The potential of Moringa oleifera leaf powder (MOLP) and Moringa oleifera leaf ethanolic extract (MOLE) to improve semen quality has been reported, but the underlying mechanisms remain unclear. For the purpose, 18 mature male cashmere goats were randomly assigned into three groups: the control (CON), MOLP, and MOLE groups. The CON group received distilled water orally; the MOLP group was orally treated with 200 mg/kg body weight (BW) MOLP; and the MOLE group was orally treated with 40 mg/kg BW MOLE. Results: Results showed that MOLE contained long-chain fatty acids and flavonoids. Treatment with MOLP and MOLE increased the activities of the serum catalase, superoxide dismutase, and glutathione peroxidase (P < 0.05), enhanced the total antioxidant capacity (P < 0.05), and reduced the serum malondialdehyde level (P < 0.05). At the same time, MOLE increased the contents of serum gonadotropin releasing hormone and testosterone (P < 0.05). Moreover, MOLE significantly increased sperm concentration, motility, and viability (P < 0.05). Meanwhile, MOLE raised the Chao1 index (P < 0.05) and altered the composition of the rumen microbiota; it also raised the relative abundance of Treponema (P < 0.05) and Fibrobacter (P < 0.05) and reduced the relative abundance of Prevotella (P < 0.1). Correlation analysis revealed the genus Prevotella was significantly negatively correlated with sperm concentration, as well as sperm motility and viability. Furthermore, MOLE significantly increased the rumen levels of the steroid hormones testosterone and dehydroepiandrosterone (P < 0.05), as well as the polyunsaturated fatty acids (PUFAs) alpha-Linolenic acid, gamma-Linolenic acid, docosapentaenoic acid, and 9-S-Hydroperoxylinoleicacid (P < 0.05). Conclusions: Oral MOLE supplementation can improve semen quality by increasing the antioxidant capacity and altering the rumen microbiota and metabolites of cashmere goats. Moreover, the MOLP supplementation could enhance the antioxidant capacity of cashmere goats.